Impact of Body Composition During Neoadjuvant Chemoradiotherapy on Complications, Survival and Tumor Response in Patients With Locally Advanced Rectal Cancer - Liu, Zhenzhen; Lu, Siyi; Wang, Yuxia; Lin, Xinyi; Ran, Peng; Zhou, Xin; Fu, Wei; Wang, Hao (Frontiers in Nutrition, 2022)
Background: To explore the impact of body composition before neoadjuvant chemoradiotherapy (pre-NCRT) and after neoadjuvant chemoradiotherapy (post-NCRT) on complications, survival, and tumor response in patients with locally advanced rectal cancer (LARC). Methods: Patients with LARC who underwent radical surgery after NCRT between January 2012 and March 2019 were studied. Body composition parameters, including skeletal muscle area (SMA), muscle density (MD), visceral fat area (VFA), total abdominal fat area (TAFA), and subcutaneous fat area (SFA), was identified at the third lumbar vertebra level on computed tomography (CT). The patients were divided into two groups based on the sex-specific quartile values of SMA, MD, VFA, TAFA, SFA, and body composition change. Patient characteristics, short- and long-term postoperative complications, survival, and tumor response were analyzed. Results: A total of 122 eligible patients were enrolled. Body composition parameters, except MD, were strongly correlated with BMI (p < 0.001). Pre-NCRT low MD (p = 0.04) and TAFA loss (p = 0.02) were significantly correlated with short- and long-term ileus, respectively. Pre-NCRT low SMA was a significant prognostic factor for both disease-free survival (DFS) (HR 2.611, 95% CI 1.129-6.040, p = 0.025) and cancer-specific survival (CSS) (HR 3.124, 95% CI 1.030-9.472, p=0.044) in the Cox regression multivariate analysis. Multivariate logistic regression analysis identified post-NCRT SFA (OR 3.425, 95% CI 1.392-8.427, p = 0.007) and SFA loss (OR 3.358, 95% CI 1.214-9.289, p = 0.02) as independent risk factors for tumor regression grade (TRG) and downstaging, respectively. Conclusion: Pre-NCRT low MD and TAFA loss were related to a high incidence of short- and long-term ileus, respectively. Pre-NCRT low SMA was a significant prognostic factor for CSS and DFS. Post-NCRT SFA and SFA loss were independent risk factors for TRG and downstaging, respectively.